Ralação entre ambiente e viabilidade polínica de híbrido de milho com macho-esterilidade citoplasmática - Panisson, Daiane Eva (2025)
Cytoplasmic male sterility (CMS) is the primary strategy for obtaining male-sterile individuals in maize cultivation and studies on maize pollen viability are fundamental, as they help to understand the mechanisms regulating fertility and contribute directly to the success of breeding programs. In this context, this study aimed to evaluate whether different environmental conditions influence the viability of pollen grains in maize hybrids produced using CMS compared to their fertile counterparts. To this end, three experiments were conducted: two in the field and one in the laboratory. In the field experiments, a maize hybrid genotype was planted in two versions, fertile (isogenic) and male-sterile (CMS), across two growing dates (2022 and 2023), with two planting periods each year (1st and 2nd). The objective was to evaluate pollen grain turgor and seed production (self-pollination). For the laboratory experiment, pollen grains were collected from plants grown in the second planting period for in vitro germination analysis and pollen viability testing using tetrazolium staining. The data collected showed differences in performance between the two versions, influenced by environmental conditions and variations in planting period and year. In the morning, the pollen turgor of the fertile version reached 9.4 and 9.2 in the 1st and 2nd planting periods, respectively, while the CMS version showed lower values of 8.4 and 7.3. The CMS version demonstrated greater vulnerability to adverse conditions, such as water restriction and low air humidity, while the fertile hybrid proved more suitable for ensuring efficient pollination in challenging environments. In terms of self-pollination, the productivity of the CMS version was 33.3% lower than the fertile version in 2022, and 20.3% lower in 2023, planting a 13.0% improvement between years. In vitro germination results showed an increase for the CMS version from 22.7% in 2022 to 52.9% in 2023, although still below the fertile version. Pollen turgor was identified as a good indicator of pollination efficiency in open fields. High temperatures and extreme relative humidity levels significantly compromised pollen viability.